The Impact of Monetary Policies on Corporate Foreign Exchange Risk Management: A Systematic Literature Review Across Emerging Economies - Lestari, Putri Ayu; Adekunle, Ahmed Oluwatobi (Sinergi International Journal of Accounting and Taxation, 2024)
Amid increasing currency volatility, effective foreign exchange risk management has become critical to maintaining corporate financial stability, particularly in emerging economies. This study examines systemic factors influencing foreign exchange risk and evaluates corporate strategies for mitigating exposure. A systematic literature review was conducted using Scopus, Google Scholar, and Web of Science, focusing on hedging strategies, policy regulations, and financial instruments. The findings indicate that firms in volatile economic environments face substantial uncertainty, with monetary policy shifts significantly affecting their hedging decisions. Moreover, companies in developing economies encounter structural barriers, including limited access to financial instruments and market intelligence. Key findings emphasize the tangible effects of monetary policies on corporate hedging behavior and highlight the urgent need for financial infrastructure reforms and risk literacy programs. This study highlights the importance of leveraging financial technologies and adopting comprehensive hedging strategies to mitigate currency risk. The insights offer practical implications for businesses and policymakers navigating the complexities of global financial exposure. Future research should explore innovative approaches tailored to diverse economic contexts to enhance corporate financial resilience against exchange rate fluctuations.